Exploring Short stories 1 - Davis, Colin (Singapore, Federal Publications, 1999)
This book was specially written to cater for the needs of lower secondary school students in Singapore. The books' key features are their excellent selections of stories, arranged by theme to help students link story with story, and their wide range of simulating activities which encourage students of all abilities to explore the ideas and situations of different stories. A new feature of this second edition of the books is the inclusion of prize-winning stories by Singapore students at the same educational levels.
A1 Fiction shelf
Keywords: English fiction story